The TLR signaling adaptor TRAM interacts with TRAF6 to mediate activation of the inflammatory response by TLR4. Issue 3 (8th May 2014) - Verstak, Brett; Stack, Julianne; Ve, Thomas; Mangan, Matthew; Hjerrild, Kathryn; Jeon, Jannah; Stahl, Rainer; Latz, Eicke; Gay, Nick; Kobe, Bostjan; Bowie, Andrew G; Mansell, Ashley
Abstract : TRAM interaction with TRAF6 regulates the inflammatory response to TLR4 activation, and adds further intricacy to TLR signaling. Abstract: TLRs act as sentinels in professional immune cells to detect and initiate the innate immune response to pathogen challenge. TLR4 is a widely expressed TLR, responsible for initiating potent immune responses to LPS. TRAM acts to bridge TLR4 with TRIF, orchestrating the inflammatory response to pathogen challenge. We have identified a putative TRAF6-binding motif in TRAM that could mediate a novel signaling function for TRAM in TLR4 signaling. TRAM and TRAF6 association was confirmed by immunoprecipitation of endogenous, ectopically expressed and recombinant proteins, which was ablated upon mutation of a key Glu residue in TRAM (TRAM E183A). TRAF6 and TRAM were observed colocalizing using confocal microscopy following ectopic expression in cells and the ability of TRAM and TRAM E183A to activate luciferase-linked reporter assays was determined in HEK293 and TRAF6-deficient cells. Importantly, TRAM-deficient macrophages reconstituted with TRAM E183A display significantly reduced inflammatory TNF-α, IL-6, and RANTES protein production compared with WT TRAM. These results demonstrate a novel role for TRAM in TLR4-mediated signaling in regulating inflammatory responses via its interaction with TRAF6, distinct from its role as a bridging adaptor between TLR4 and TRIF.